Archive Management of Tienuk Riefki: Strategies And Solutions - Rulli Meilia (TUMATA: Journal of Arts and Cultural Management, 2023)
The curation of “Tienuk Riefki Archives and Memorabilia Exhibition: Maestro of Javanese Tradisional Bridal Makeup Art” made this choice derived from the culture and values contained in tradisional bridal makeup. Tienuk Riefki is one of the bridal makeup artists who still adheres to the standard. The method used is a qualitative method in which the variable is a means or a tool to analyze and the author will examine a problem with an individual or certain in depth with a historical approach. This method is used to find out about personal, and tradisional Javanese bridal makeup, especially Yogyakarta. The process of implementing the practice of curation in the "Tienuk Riefki Archives and Memorabilia Exhibition: Maestro of Javanese Tradisional Bridal Makeup Art" is carried out in stages from the idea of an exhibition, beginning, forming an implementing team, site selection, selection, scenography, circulation, work display layout, publications and promotions, events, and evaluations. Through the curation of “Tienuk Riefki Archives and Memorabilia Exhibition: Maestro of Javanese Tradisional Bridal Makeup Art”, it is hoped that it can provide benefits and information about make-up and also invites artists to be more concerned with archives, especially maestro archives.